LEMBAR KERJA DINAMIS GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PENALARAN ANALOGIS SISWA - Sendi Ramdhani (Journal of Learning and Technology, 2022)
This study aims to develop GeoGebra Dynamic Worksheets to enhance students' analogical reasoning abilities. Students are expected to interact with GeoGebra Dynamic Worksheets or Dynamic Activities. This research used Design Didactical Research (DDR). Based on the learning obstacles faced by students when carrying out the analogical reasoning process, the GeoGebra Dynamic Worksheet was developed as follows: 1) Reinforcement of the retrieval process: The GeoGebra Worksheet is designed so that students remember in advance about the material or situation that is analogous to the material to be discussed; 2) Strengthening the mapping process: GeoGebra Dynamic Worksheets are designed so that students are able to align the previous analog situation with the new analog situation; 3) Strengthening the evaluation process: several questions are displayed on the Dynamic Worksheet.